Virtual 3D modeling in trans-areola single-site endoscopic thyroidectomy for large nodular goiter: a report of 33 cases - CHEN Lingxie, XUAN Ming, DING Hao, ZHANG Yongchang, CHEN Cheng, KUANG Jie, YAN Jiqi, QIU Weihua, TAN Jian (Waike lilun yu shijian, 2020)
Objective To evaluate virtual 3-dimensional (3D) modeling in treatment of large nodular goiter (length≥3 cm) via trans-areola single-site endoscopic thyroidectomy (TASSET). Methods Clinical data with 33 patients who received TASSET for large nodular goiter from June 2017 to January 2019 were investigated retrospectively. All patients underwent preoperative localization by CT and ultrasonography. Digital technique was utilized to build the virtual 3D mo-deling for nodular localization and digital surgical planning. Clinical data including the location and size of nodules, operative time, pathological results, and complications were analyzed. Patients were followed-up postoperatively for therapeutic outcome. Results All patients underwent TASSET successfully followed the preoperative digital surgery planning without conversion to open surgery. There were 19 cases with left thyroid nodules and 14 cases with right thyroid nodules. Mean length of nodule was (37.3±7.2) mm with operative time (107.6±23.6) min. Pathological examination showed 18 cases of nodular goiter, 8 cases of follicular adenoma, 4 cases of Hürthle cell adenoma, 2 cases of lymphocytic thyroiditis, and 1 case of toxic thyroid adenoma. No postoperative complication was observed. Patients were followed-up during 7 to 26 months without residual thyroid or recurrence. Conclusions Preoperative application of 3D digital technique to build visualization model for nodule localization and surgery planning could reduce operative risk and improve the safety and effectiveness of TASSET in treatment of large nodular goiter.